Visual Characteristics of Drawings from Students in Lower Grades of Elementary School - Nurcahyo, Lintang; Martadi, Martadi; Lodra, I Nyoman (Universitas Negeri Malang, 2022)
Students in a lower grade of elementary school have started to use pictures from theirobservation oftheir environment and constructed ideas until they arrive atthe early realism stage. Using qualitative approach and samples from pictures of students in lower grades of elementary schools, this study concluded that the visual characteristics of theirpictures are constructive thinking as affected by their environment and personality. Their learning tendency uses concrete, integrative, and hierarchical with the drawing typesof visual, haptic, and amixture of them. Most drawingsare characterized as stacked, laying down, covering each other, bird perspective, and object reduction, with four dominating visual elementsof line, area, shape, and color